Fiscal decentralization, governance quality, and regional disparities in Uruguay - Muinelo Gallo, Leonel; Rodríguez Miranda, Adrián (Estudios de Economía, 2015)
In this paper we analyze the mediating role of governance quality in the relationship between fiscal decentralization and regional disparities. Previous work has argued that fiscal decentralization has the potential to reduce income differences across regions but that this potential may not be realized because of governance problems associated with sub-national authorities. Our empirical evidence based on a sample of departments (regions) of Uruguay over the period 1990-2010 lends support to this idea. The empirical results show that fiscal decentralization promotes regional convergence, and this effect is boosted in high governance quality settings.